Acute toxicity and potentiation of barbiturate-induced sleep in mice orally treated with hydro-alcoholic extract of Cyclolepis genistoides D. Don. (Asteraceae) - Yenny Montalbetti Moreno, Derlis A. Ibarrola, Olga Heinichen, Nelson Alvarenga, Julio. H. Dolz Vargas, Maria C. Hellion-Ibarrola (Journal of Applied Pharmaceutical Science, 2018)
The aims of this work were to determine the acute toxicity, the influence on general behavior, motor coordination, barbiturate-induced sleeping time in mice, and the chemical constituents of a hydro-alcoholic extract of the Cyclolepis genistoides D. Don. (Asteraceae) (CE-Cg). The presence of triterpenes, sesquiterpene lactones, and saponins was detected by preliminary phytochemical testing of CE-Cg. No lethal sign was observed up to 3,000.0 mg/kg (po) or 1,500.0 mg/kg bw (ip) of CE-Cg administered to mice. Oral doses of 10.0, 100.0, and 1,000.0 mg/kg bw of the CE-Cg significantly prolong the sleeping time induced by barbiturate and ethyl ether when compared with the control group. Motor coordination performance in rota-rod and chimney test was not modified by oral treatment with CE-Cg (1.0, 10.0, 100.0, and 1,000.0 mg/kg bw) when compared with the control group. Therefore, based on these findings, we concluded that the hydro-alcoholic extract of the C. genistoides D. Don. is safe, well tolerated without disturbing motor coordination orally and shows significant hypnotic property in mice. Consequently, C. genistoides is potentially a good candidate to develop a phytotherapeutic agent for a complementary treatment of insomnia and encourages us to pursue specific and complementary chemical and pharmacological evaluation at Central nervous system (CNS) level.
Keywords: Cyclolepis genistoides D. Don., Palo azul, LD50, general behavior, sleep time.